(untitled) (Bangladesh Journal of Plant Taxonomy, 2025)
Splachnum ampullaceum Hedw., Sphagnum capillifolium (Ehrh.) Hedw., and Plagiothecium cavifolium (Brid.) Z. Iwats. have been reported as new for Azerbaijan, following a recent bryological expedition to the Tugay forest and Dilman forest of Azerbaijan. Of these, Splachnum has been recorded as new genus record for bryophyte flora of Azerbaijan. Brief descriptions, illustrations, geographic distribution, ecology and comparisons with morphologically similar species are presented. Bangladesh J. Plant Taxon. 32(1): 45-52, 2025 (June)